Cross-CRP Analysis of Theories of Change in the 2017-2022 in CRP2 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
This brief examines the CGIAR Research Program Portfolio (CRP2) proposals to comment on the Theory of Change and Impact Pathways contained within three interlinked clusters of initiatives: Innovation in Agri-Food Systems, Global Integrating Programs, and System-Level platforms.